Social Protection in Prevention And Management of High-Risk Stunting Families in Palangkaraya City - Lalu Satria Utama; Siti Nur Aini Najib; Eva Eviany; Dwi Putri Yuliani (Journal of Governance, 2024)
The problem of stunting is an issue of concern because it involves the sustainability of human resource development and needs to be protected. The results of the Indonesian Nutrition Status Survey 2019-2022 stated that Palangkaraya City continued to experience an increase in stunting rates. Objective: To explain the efforts made by the Palangkaraya City Government to prevent and handle families at risk of stunting from a social protection perspective. Methods: This research uses a descriptive qualitative research method with an inductive approach. The data collection techniques used by researchers are interviews, observation, documentation, and data triangulation. The theory used is the Social Protection Theory by Sabates Wheeler-Deveureux (2007). Results: The DisdaldukKBP3APM of Palangkaraya City is constrained by recording and collecting stunting data that is not yet explorative and integrative, as well as constraints in sharpening interventions for families at risk of stunting in Palangkaraya City. Conclusion: The conclusion is that DisdaldukKBP3APM of Palangkaraya City has pursued various promotional, preventive, protective, and transformative programs well in preventing and handling families at risk of stunting.